2004
DOI: 10.1002/ccd.10769
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of right or left radial approach for coronary angiography

Abstract: The transradial approach for catheterization is becoming increasingly more popular. At present, the choice of the right or left radial artery depends on the operator's preference. We examined how the laterality influenced the effectiveness of the approach. Employing Judkins-type catheters, we performed coronary angiography in 232 patients with the left approach and in 205 patients with the right approach. Although access time did not differ between the two groups of patients, the duration of catheter manipulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
33
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 35 publications
8
33
0
2
Order By: Relevance
“…Conversely, operator positions and insertion sites near the edge of the x-ray beam can result in a higher operator dose. During PM or ICD implantation, the operator generally uses a subclavian approach, as opposed to the femoral or radial/brachial approach used for other procedures (Kawashima et al 2004). The subclavian approach requires the operator to stand close to the patient's shoulder and adjacent to the x-ray tube, where exposure rates are considerably higher than for the radial/brachial approach (Lindsay et al 1992;Limacher et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, operator positions and insertion sites near the edge of the x-ray beam can result in a higher operator dose. During PM or ICD implantation, the operator generally uses a subclavian approach, as opposed to the femoral or radial/brachial approach used for other procedures (Kawashima et al 2004). The subclavian approach requires the operator to stand close to the patient's shoulder and adjacent to the x-ray tube, where exposure rates are considerably higher than for the radial/brachial approach (Lindsay et al 1992;Limacher et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…At present, the right radial approach (RRA) has become the first choice for the performance of routine coronary angiography and interventions for comfort reasons in daily clinical practice despite more marked subclavian artery tortuosity 9. Although the left radial approach (LRA) may reduce fluoroscopy time and cerebrovascular complications compared with RRA,1012 several studies have also obtained conflicting results 1316. Additionally, most of the investigations evaluating the efficacy of the transradial approach have been conducted among Caucasian persons.…”
Section: Introductionmentioning
confidence: 99%
“…Louvard et al 25 reported the volume of contrast was similar in radial and femoral approaches for CAG. Kawashima et al 28 reported the amount of contrast material in CAGdid not differ between the left radial and right radial approach group (79±27 vs. 83±25 mL; p>0.05).Khan and Kabir 29 reported a trend toward a lower dose of contrast media used during diagnostic coronary procedures in the left radial approach compared with the right radial approach (37±16 and 47±11.9 mL respectively, p =0.006) in 512 diabetic patients.…”
Section: Discussionmentioning
confidence: 96%
“…Louvard et al 27 reported fluoroscopy time was significantly shorter in the femoral group (3.1±1.7 min) than in both radial groups (right: 3.8±2.2 min; left: 4.2±1.7 min), p <0.01. Kawashima et al 28 reported the fluoroscopy time in CAGwas shorter in the left radial than in the right radial approach group (3.7 ± 2.5 vs. 5.0 ± 3.3 min;p <0.001). Again Louvard et al 25 conducted another study to compare TR and TF approaches for CAGand angioplasty in octogenarians and they reported that fluoroscopy time was shorter in the femoral group versus the radial group (4.5±3.7 vs. 6.0±4.4 min; p <0.05) for the CAG.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation